Pola Asuh Orang Tua Tepian Sungai terhadap Anaknya di Desa Segati, Langgam, Pelalawan, Riau - Ayu Zarmita Sari; Daeng Ayub (Fakultas Syariah IAIN Laa Roiba Bogor, 2023)
This study aims to determine and analyze the parenting patterns of parents on the banks of the segati river to their children in segati village, Langgam district, Pelalawan regency. this research uses qualitative descriptive research. Qualitative research aims to describe the reality of a phenomenon that occurs carefully. Data collection used decumentation, observation and interviews about the parenting of the segati riverside parents. The results showed that the parenting style used by parents on the banks of the Segati river, Langgam District, Pelalawan Regency, in educating, caring for and caring for their children using a combined parenting style, namely using authoritarian parenting, democratic parenting, fathernalistic parenting and charismatic parenting. In addition, of the five existing parenting styles, laissez-faire parenting is a parenting style that is not used by people on the banks of the Segati river in caring for their children in Segati village, Langgam District, Pelalawan Regency. Keywords: Parenting, parent, child